Failure mechanisms and loading capacity prediction for rectangular UHPC beams under pure torsion. (1st August 2022) - Li, Chuanxi; Zhou, Jiale; Ke, Lu; Yu, Shuo; Li, Haichun
Highlights: Twelve rectangular UHPC solid beams subjected to pure torsion are fabricated and tested. The additional steel fibers substantially improved the torsional behavior. The failure modes of UHPC members, including two different modes, are identified, and the definitions of these failure modes evolve with new connotations. The effective reinforcement ratio (1.32%) is proposed in this paper, which is mainly directly depended upon the steel fibre volume fraction. A formula was proposed to predict the ultimate torsional strength for UHPC rectangular solid beams, and the application was verified by the experimental data available in reference and a reliability analysis. Abstract: This study presents an experimental investigation of the loading capacity and failure mechanism of ultra-high-performance concrete (UHPC) beams under pure torsion. Twelve rectangular solid beams were fabricated and tested. The investigated parameters include the volumetric fraction of steel fibers (1.5%, 2.5%, and 3.5%), the longitudinal reinforcement ratio (0–1.54%), and the stirrup ratio (0–1.29%). The torsional behavior, including the crack propagation and failure modes, torque–twist curves, torque–strain curves, cracking and ultimate strengths, and effectiveness of steel fibers were evaluated and presented. Considering the UHPC high tensile strength, a formula for UHPC solid beams was proposed and verified by a reliability analysis. The results showed that compared to conventional concrete beams, the UHPC beams exhibited similar suitably reinforced, partially over-reinforced, and over-reinforced failure modes. Additionally, two different failure modes (type-I and type-II barely reinforced) were identified for UHPC beams. The additional steel fibers improve the torsional properties and directly determine the effective reinforcement ratio. Moreover, the steel fibers with 1.5% or higher volume fractions were proven to be sufficient to replace stirrups, and the proposed formula is effective in predicting the torsional strength of UHPC rectangular solid beams.